2019
DOI: 10.3389/fpsyt.2019.00531
|View full text |Cite
|
Sign up to set email alerts
|

Body Image as Well as Eating Disorder and Body Dysmorphic Disorder Symptoms in Heterosexual, Homosexual, and Bisexual Women

Abstract: Body image disturbance is a core symptom of eating disorders (EDs) and body dysmorphic disorder (BDD). There is first evidence that females’ body image differs depending on sexual orientation, with heterosexual women (HEW) appearing to show more body image disturbance symptoms than homosexual women (HOW). Such disparities might be moderated by everyday discrimination experiences and involvement with the lesbian community. However, to date, there has been no comprehensive assessment of a broad range of body ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 89 publications
6
23
0
Order By: Relevance
“…Our results only partially confirmed our hypothesis, but they are in line with data from the literature that indicate that BIW and gay men are more likely to have body concerns than their heterosexual peers [24,60,61]. Indeed, data from recent studies suggest that BIW feel pressured to integrate physical norms from both the heterosexual and lesbian cultures and are significantly vulnerable to body dissatisfaction, even if results are not unique [8,25]. According to our results, sexual minority men are more prone than the other cisgender groups to internalize social pressure about body evaluation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results only partially confirmed our hypothesis, but they are in line with data from the literature that indicate that BIW and gay men are more likely to have body concerns than their heterosexual peers [24,60,61]. Indeed, data from recent studies suggest that BIW feel pressured to integrate physical norms from both the heterosexual and lesbian cultures and are significantly vulnerable to body dissatisfaction, even if results are not unique [8,25]. According to our results, sexual minority men are more prone than the other cisgender groups to internalize social pressure about body evaluation.…”
Section: Discussionsupporting
confidence: 90%
“…Body image is influenced by cultural factors, interpersonal skills, physical changes over time, personality characteristics, selfesteem, and quality of life [4][5][6][7]. Recently, the literature has considered genders and sexual orientations as significant factors that might have a significant effect on one's body evaluation, but bisexual women and men are often misrepresented in the literature and included with other sexual minorities [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…At the individual level, LGB youth were signi cantly more likely to report unhealthy weight-control behaviors in line with Lucassen et al [28] Our ndings also showed that at the individual level, there was some mediation of that association among LGB youth by personal experiences of bullying victimization and perceived low happiness. Our ndings are consistent with previous studies [23,29] showing that minority stress is associated with unhealthy weight control behaviors in sexual minority youth. Regarding the interaction between LGB x gender at individual level, LGB boys were not signi cantly more likely to engage in unhealthy weight-control, although the direction of association was in the expected direction, in line with Hadland et al [30] However, the bigger picture from our study is that low LGB visibility is correlated with unhealthy weightcontrol behaviors in all students.…”
Section: Discussionsupporting
confidence: 93%
“…[21,22] Experiences of discrimination were associated with eating disorders and body image disturbance in all groups of women (homosexual, heterosexual and bisexual). [23] In the present study we sought to examine the association between heteronormativity (as proxied by the prevalence of LGB youth in schools) and unhealthy weight-control behaviors among sexual minority youth.…”
Section: Introductionmentioning
confidence: 99%
“…94,95), we did not analyze these persons in the present study due to the insufficient sample size (N = 7). Moreover, we did not investigate the relation between sexual orientation and body image, although previous studies have found indications of an influence of sexual orientation on body image (96)(97)(98)(99). Therefore, future research should investigate the impact of age on body image for different sexual orientations.…”
Section: Discussionmentioning
confidence: 93%